Recovery of uranium from residue generated during Mo-99 production, using organic solvent extraction. (February 2020) - Mokhine, Naomi D.; Mathuthu, Manny; Stassen, Elizabeth
Abstract: During the production of the medical isotope Mo-99, the uranium and some fission products are precipitated as residue of mixed hydrated oxides. However, the PUREX extraction of uranium, plutonium is extracted, raising proliferation issues. The aim of this research was to characterize the most effective organic solvent for the recovery of uranium. Uranium oxide was dissolved in ammonium carbonate solution to form uranium tri-carbonate aqueous feed solution. Results show that 0.2 M ammonium carbonate and 0.01 M uranium mixed with 15% Aliquat 336 in Toluene at volume ratio (A/O) of 1:5 produced 98% extraction of uranium from the alkaline media. Highlights: Solvent extraction technique of uranium from alkaline nuclear waste is proposed. Toluene in 15% Aliquat 336 was found to be the most effective organic extractant. 0.2 M Ammonium carbonate and 0.01 M uranium were the optimum concentrations. Uranium extraction percentage of 98% was achieved at a phase volume ratio of 1:5.